2017
DOI: 10.1007/s10571-017-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Involved Key Genes and Signaling Diversity in Brain Tumors

Abstract: Brain tumors are becoming a major cause of death. The classification of brain tumors has gone through restructuring with regard to some criteria such as the presence or absence of a specific genetic alteration in the 2016 central nervous system World Health Organization update. Two categories of genes with a leading role in tumorigenesis and cancer induction include tumor suppressor genes and oncogenes; tumor suppressor genes are inactivated through a variety of mechanisms that result in their loss of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 156 publications
0
15
0
Order By: Relevance
“…A long‐scale study conducted by The Cancer Genome Atlas (TCGA) revealed numerous data on specific genetic and epigenetic alterations underlying gliomas . Although it is still not possible to define the exact number and chronology of changes during gliomagenesis, they found that key genes responsible for the formation and progression of astrocytic brain tumours are most frequently involved into deregulated oncogenic pathways: RTK/RAS/PI3K, TP53 and RB . Recent studies have shown that altered signal transduction in Wnt signalling pathway is also involved in the molecular pathogenesis of glial tumours …”
Section: Introductionmentioning
confidence: 99%
“…A long‐scale study conducted by The Cancer Genome Atlas (TCGA) revealed numerous data on specific genetic and epigenetic alterations underlying gliomas . Although it is still not possible to define the exact number and chronology of changes during gliomagenesis, they found that key genes responsible for the formation and progression of astrocytic brain tumours are most frequently involved into deregulated oncogenic pathways: RTK/RAS/PI3K, TP53 and RB . Recent studies have shown that altered signal transduction in Wnt signalling pathway is also involved in the molecular pathogenesis of glial tumours …”
Section: Introductionmentioning
confidence: 99%
“…Mechanism of long term resting state is unclear in brain tumors. 18) Recent report shows that Notch and WNT signaling pathway relates to cell cycle and re-activation of proliferation cycle in meningioma and astrocytoma. 18) Expression of these signaling factors might contribute to predict future recurrence and be useful as a marker of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Bar charts were used to illustrate the number of genes that overlap in both KEGG pathways and functional annotation clusters. Moreover, dot matrices were computed to reflect the impact of genes associated with each KEGG pathway as well as enrichment maps and GSEA plots (Morgan et al, 2017). Matrix layout for all genes within 18 KEGG pathways sorted by size.…”
Section: Computation Analysis Of Cnasmentioning
confidence: 99%